2022
DOI: 10.3389/fvets.2022.703051
|View full text |Cite
|
Sign up to set email alerts
|

Integrated 16S rDNA Gene Sequencing and Untargeted Metabolomics Analyses to Investigate the Gut Microbial Composition and Plasma Metabolic Phenotype in Calves With Dampness-Heat Diarrhea

Abstract: Dampness-heat diarrhea (DHD), a common syndrome in Chinese dairy farms, is mainly resulted from digestive system disorders, and accompanied with metabolic disorders in some cases. However, the underlying mechanisms in the intestinal microbiome and plasma metabolome in calves with DHD remain unclear. In order to investigate the pathogenesis of DHD in calves, multi-omics techniques including the 16S rDNA gene sequencing and metabolomics were used to analyze gut microbial compositions and plasma metabolic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Diarrhoea alters the composition of the intestinal microbiome of calves. Research (Yan et al, 2022) found changes in 14 genera, which included Bacteroides, Shigella, Fournierella, Escherichia.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoea alters the composition of the intestinal microbiome of calves. Research (Yan et al, 2022) found changes in 14 genera, which included Bacteroides, Shigella, Fournierella, Escherichia.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, the modeling methods and the results of symptoms in the model mice were consistent with the diagnostic criteria of DSH, indicating that the model was successfully replicated ( Hui et al., 2021 ). The main clinical sign of diarrhea with DSH is closely related to gut microbiota dysbiosis ( Gong et al., 2015 ; Yan et al., 2022 ). Studies have shown that digestive tract diseases occur primarily due to structural changes in bacteria of typical origin ( Sorbara and Pamer, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The calves were fed colostrum at a dose of 4 kg/calf only on the first day of postpartum, and then fed the pasteurized normal milk at a dose of 6 kg/day, and the calf feed was fed from the third day of postpartum, and the feeding and drink tools were washed and disinfected two times daily. The diagnosis of calves with DHD followed the protocol in our previous study ( 12 ), which means that the DHD case was mainly characteristic with diarrhea as well as the symptom of red tongue coated with thick greasy tongue-fur or the symptom of feces with mucus, blood, or purulence. At the same time, the DHD case must show two out of total minor symptoms in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, metabolomics was used to study the mechanism of diarrhea in calves, and acetylcarnitine, indoxyl sulfate, and oxindole have been recognized to be potential biomarkers for calf diarrhea ( 11 ). Additionally, metabolites such as lecithin and choline have been found to affect the progression of DHD by interfering with the metabolism of arachidonic acid, linoleic acid, and glycerophospholipids in calves ( 12 ). Previous studies on the structure and function of fecal microflora of calves with DHD indicated that DHD had a significant effect on the intestinal microbial compositions in calves, including significant changes in Escherichia-Shigella, Bacteroides, and Fournierella in sick calves ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation